Policies Relating to Criminal Economic Law to Overcome the Covid-19 Pandemic in Indonesia - Simanjuntak, Apri Ando; Nasution, Firmansyah (Syntax Literate, 2024)
The legal vacuum (leemten in het recht) surrounding Criminal Economic Law in Indonesia amid the unprecedented Covid-19 pandemic necessitates the formulation of appropriate legal policies to address this novel phenomenon. This study aims to elucidate the existing legal policies pertaining to Criminal Economic Law in Indonesia and to propose policies specifically tailored to mitigate the impact of the Covid-19 pandemic. Adopting a normative legal research approach with a legislative and conceptual focus, the study examines both substantive and procedural legal aspects. The findings reveal two main categories of policies: those of substantive law and procedural law. These policies strive to strike a balance between providing deterrence against economic crimes while considering the unique challenges posed by the Covid-19 pandemic. In conclusion, the study underscores the importance of formulating legal policies that reflect proportional justice, effectively deterring economic crimes while considering the context of the ongoing public health crisis.